Evaluasi Ketersediaan Koleksi Berdasarkan Referensi RPS di Perpustakaan Universitas Ahmad Dahlan (Studi Kasus Prodi Ilmu Komunikasi) - Ana Pujiastuti (Pustakaloka, 2022)
The abundance of collections in the College Library is not always proportional to the level of adequacy of the reference needs of its users. To make this happen, UAD Library held activities to identify the availability of MKI and MKTP references. The purpose of this study is to identify collections based on the RPS reference of the Communication Science Study Program and analyze the factors that influence it. This research is a combination of qualitative and quantitative research. The data of this study were obtained from references in the RPS of the Communication Science Study Program. Data collection techniques using the method of documentation, observation and interviews. While the data analysis technique using the checklist method. Based on the research that has been done, it can be concluded that the availability of reference collections for the Communication Studies Study Program for MKI is included in the less fulfilling category by 58%. Meanwhile, MKTP is included in the category of sufficient to meet 71%. Findings that have not reached the 80% collection availability standard are due to several factors, such as old books that are hard to find or books that are no longer published. Meanwhile, to meet the needs of users, UAD Library held a reference with a similar theme. The percentage of collection availability has not been maximized because there is no detailed communication with Study Program regarding new references that can be added to the RPS which will create continuity between the books needed through the references listed in the RPS and the books provided in the UAD Library.